2013
DOI: 10.1016/j.jns.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Zoster paresis: Asymptomatic MRI lesions far beyond the site of rash and focal weakness

Abstract: We describe a patient with zoster paresis and an MRI that revealed extensive spinal cord lesions from the upper cervical to the lower thoracic spinal cord. Importantly, the patient reported considerable spontaneous improvement in strength 2-3 weeks after zoster. This report reveals a previously undescribed remarkable preponderance of MRI lesions far beyond the site of zoster rash and focal lower motor neuron weakness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Haanpää et al described focal nonenhancing brainstem hyperintense lesions in T2-weighted images in patients with trigeminal zoster without extraocular muscle involvement [ 4 ]. Our MRI findings demonstrated an even longer spreading of the abnormal hyperintensity signal on T2W compared to a case report by Tsai et al which described a long enhancing lesion from upper cervical cord extending to the lower thoracic spinal cord [ 6 ].…”
supporting
confidence: 48%
“…Haanpää et al described focal nonenhancing brainstem hyperintense lesions in T2-weighted images in patients with trigeminal zoster without extraocular muscle involvement [ 4 ]. Our MRI findings demonstrated an even longer spreading of the abnormal hyperintensity signal on T2W compared to a case report by Tsai et al which described a long enhancing lesion from upper cervical cord extending to the lower thoracic spinal cord [ 6 ].…”
supporting
confidence: 48%
“…Whereas several cases report no pathologic findings in a MRI, 10-13 there is proof that a MRI can show nerve enlargement or enhancement. 13-15 One study showed the variation of imaging abnormalities based on the electrodiagnostic localization of the lesions. 16 In patients with preganglionic electrodiagnostic lesions the MRI showed no abnormalities.…”
Section: Discussionmentioning
confidence: 99%